ANALISIS PERBANDINGAN PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) DI NEGARA BERKEMBANG DAN NEGARA MAJU (INDONESIA DAN SINGAPURA) - Fatmawati, Merine Mistin; Nawangsari, Ajeng Tita (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
The researcher explained about the comparison of the implementation of Good Corporate Governance (GCG) in developing countries and developed countries, namely Indonesia and Singapore. The research was conducted with the aim of understanding the differences and similarities in corporate governance practices between the two countries. Indonesia, as a developing country, has its own challenges in implementing GCG due to the complexity of corporate structures, varying levels of industrial maturity, and diverse corporate cultures. The research method used is a qualitative method using a literature review that classifies articles based on books, scientific journals, articles, research reports, and relevant sources. The research results produce information about the differences in the implementation of GCG in Indonesia and Singapore due to differences in both regulations and measurement indices in each country.